2020
DOI: 10.3390/metabo11010026
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Targeted Lipidome Analyses (Lipidyzer) in Plasma and Erythrocytes over a 6-Week Period

Abstract: It is essential to measure lipid biomarkers with a high reproducibility to prevent biased results. We compared the lipid composition and inter-day reproducibility of lipid measurements in plasma and erythrocytes. Samples from 42 individuals (77% women, mean age 65 years, mean body mass index (BMI) 27 kg/m2), obtained non-fasted at baseline and after 6 weeks, were used for quantification of up to 1000 lipid species across 13 lipid classes with the Lipidyzer platform. Intraclass correlation coefficients (ICCs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Considering these circumstances, three sites robustly measured more than 500 lipid species in the cohort plasma samples. A recent study on reproducibility of targeted lipidome analyses in plasma and erythrocytes using the Lipidyzer platform also reported that 491 lipid measurements in plasma were reproduced well over a 6 week period . This promising number of robustly measured lipids puts the platform in a strong position to be used in important clinical research and biomarker discovery studies.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering these circumstances, three sites robustly measured more than 500 lipid species in the cohort plasma samples. A recent study on reproducibility of targeted lipidome analyses in plasma and erythrocytes using the Lipidyzer platform also reported that 491 lipid measurements in plasma were reproduced well over a 6 week period . This promising number of robustly measured lipids puts the platform in a strong position to be used in important clinical research and biomarker discovery studies.…”
Section: Resultsmentioning
confidence: 91%
“…A recent study on reproducibility of targeted lipidome analyses in plasma and erythrocytes using the Lipidyzer platform also reported that 491 lipid measurements in plasma were reproduced well over a 6 week period. 32 This promising number of robustly measured lipids puts the platform in a strong position to be used in important clinical research and biomarker discovery studies. At present, it is still a challenging task to reproduce clinical metabolomics findings between laboratories, with the major impediment being the limited methodological and practical agreement among laboratories.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results suggested that sphingolipids overload in RBCs could occur during erythropoiesis [41]. Also as recently reported that differences at individual levels in plasma may favor the use of erythrocytes [42] our study investigated the best protocol to do that by using the minimum volume of whole blood and the relevant internal standards for normalization. We will move next to a case-control study of a particular disease to show the applicability of this new approach.…”
Section: Discussionmentioning
confidence: 99%
“…The LOQ for all the sphingolipids investigated here allows the use of only 10-μl WB. A recent study looking at the basal lipids level in healthy volunteers over a 6 weeks period in plasma and erythrocytes reported that reproducibility in ceramides, diacylglycerols and sphingomyelins was better in erythrocytes [ 39 ]. To reduce any artifacts that could results from erythrocytes isolation, our study investigated the best protocol to use WB, by using the minimum volume necessary for accurate quantification and the relevant ISs for normalization.…”
Section: Discussionmentioning
confidence: 99%